IMPACT OF A PRECISE GEOID MODEL IN STUDYING TECTONIC STRUCTURES-A CASE STUDY IN IRAN - Kiamehr R.; Sjöberg L.E. (My University, 2006)
Iran is one of the most active regions in the world with respect to earthquakes and tectonic motions in the lithosphere. In order to study the impact of the geoid model in detecting plate tectonic boundaries and in the establishment of an accurate height datum for future geodynamic observations, a new combined gravimetric geoid model for Iran (IRG04C) was computed by the method of least squares modification of Stokes formula based on the most recent gravity anomaly database, SRTM high resolution Digital Elevation Model (DEM), GRACE GGM02 Global Geopotential Model and GPS/levelling data. The RMS fit of the new geoid model versus GPS/levelling data is 9 cm, which is a 10 times better fit compared to the most recent published gravimetric geoid model in the area. An integrated approach, combining gravity, geoid and seismology data as well as a digital elevation model, was used to find possible correlations between these parameters. Our investigation indicates that all earthquakes with magnitude over 6.0 in the Richter scale are located in areas with a geoid slope exceeding 7.5%. The study shows a significant correlation between the horizontal gradient of the geoid and plate tectonic activities. © 2006 Elsevier Ltd. All rights reserved.
Keywords: GPS/LEVELLING; GRACE; IRAN; LATERAL GEOID SLOPE; PLATE TECTONICS; SRTM